Assessment of monetary and credit policies in the OECS region 1975-1985 - Liburd, E.E. (Institute of Social and Economic Research KingstonJM, 1986)
Describes monetary and institutional arrangements in the OECS region. Considers economic structure and performance of the OECS countries. Provides data on the money supply process during 1975-1985 showing growth rates for both 'narrow' and 'broad' money. Examines use of monetary instruments and appraises the effectiveness of monetary and financial policies over the period under consideration.